2021
DOI: 10.1371/journal.pone.0255152
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes after exposure to crisis pregnancy centers among an abortion-seeking sample recruited online

Abstract: Introduction More than 2,500 crisis pregnancy centers (CPCs), which seek to convince people considering abortion to continue their pregnancies, exist in the United States. However, the characteristics of people who visit CPCs and their pregnancy outcomes are largely unknown. This study sought to describe the characteristics of people considering abortion who report visiting CPCs, and whether CPC visit is associated with abortion or continuing the pregnancy 4 weeks later. Methods Between August 2017 to May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Furthermore, a recent study demonstrates that nearly half of abortion patients went to their nearest provider and 32% chose their facility because it was the closest (Fuentes and Jerman, 2019). Another study concludes that proximity to a CPC increases the likelihood of ending up at one (Cartwright et al, 2021). We expand upon this scholarship by centering CPCs in our examination of the relationship between driving time and abortion access.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study demonstrates that nearly half of abortion patients went to their nearest provider and 32% chose their facility because it was the closest (Fuentes and Jerman, 2019). Another study concludes that proximity to a CPC increases the likelihood of ending up at one (Cartwright et al, 2021). We expand upon this scholarship by centering CPCs in our examination of the relationship between driving time and abortion access.…”
Section: Methodsmentioning
confidence: 99%
“…As of 2019, there were 738 abortion facilities in the United States, less than one third of the number of CPCs. Nearly 90% of U.S. counties have no abortion provider (Jones and Jerman, 2017), a number that increases to 97% in rural areas (Finer and Henshaw, 2003). Perhaps more to the point, considering that patients seeking abortions do not necessarily go to the nearest facility in their county—they go to the nearest facility regardless of jurisdiction—scholars have used driving time to analyze reproductive health disparities (Bearak et al, 2017).…”
mentioning
confidence: 99%
“…Biased counseling requirements often include referrals to Crisis Pregnancy Centers (CPCs), which try to convince women considering abortion to continue their pregnancies (Swartzendruber et al 2019). Research on the effects of CPCs on abortion-seekers has found that they are less likely to obtain an abortion and more likely to still seek one than those who did not visit a CPC (Cartwright et al, 2021). States that refer abortion patients to CPCs also often have gag rules that prohibit employees who receive state funds from discussing abortion or referring women to abortion providers.…”
Section: Laws That Aim To Dissuade Abortionmentioning
confidence: 99%
“…In addition to the purposefully deceptive nature and explicit anti-abortion objectives of CPCs, engagement with CPCs may also lead to direct harms for both pregnant and non-pregnant women. Individuals seeking pregnancy confirmation at CPCs not only experience delays in accessing abortion care when desired, 23 , 43 but in the case of desired pregnancies, may also experience delayed entry into prenatal care or delayed recognition of pregnancy complications or medical conditions as a result of visiting a non-licensed clinic. 23 , 43 A recent survey study conducted with 607 CPCs in 9 states found that only 5% directly offered prenatal care, while only 40% provided referrals for prenatal care.…”
Section: Additional Harms Associated With Cpcsmentioning
confidence: 99%
“…Individuals seeking pregnancy confirmation at CPCs not only experience delays in accessing abortion care when desired, 23 , 43 but in the case of desired pregnancies, may also experience delayed entry into prenatal care or delayed recognition of pregnancy complications or medical conditions as a result of visiting a non-licensed clinic. 23 , 43 A recent survey study conducted with 607 CPCs in 9 states found that only 5% directly offered prenatal care, while only 40% provided referrals for prenatal care. 17 The same study found that only 26% and 16% of CPCs have a registered nurse or physician on staff, respectively, which underscores that individuals attending CPCs are not receiving medical care, and potentially dangerous diagnoses such as ectopic pregnancy may be missed.…”
Section: Additional Harms Associated With Cpcsmentioning
confidence: 99%